Secondary IGF-I Deficiency as a Prognostic Factor of Growth Hormone (GH) Therapy Effectiveness in Children with Isolated, Non-acquired GH Deficiency - Smyczyńska, J.; Stawerska, R.; Hilczer, M.; Lewiński, A. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Objective: Growth hormone (GH) deficiency (GHD) has recently been classified as secondary IGF-I deficiency but the significance of IGF-I measurement in diagnosing GHD is still discussed. The aim of the study was to assess the relationships between IGF-I secretion and GH therapy effectiveness in children with GHD.Patients and methods: The analysis comprised 300 children with isolated, non-acquired GHD (GH peak below 10 μg/l) who completed GH therapy and attained final height (FH). In all patients IGF-I concentration was measured before the treatment and IGF-I deficiency was diagnosed if IGF-I SDS for age and sex was below −1.0. The following auxological indices were assessed: patients’ height SDS before treatment (H0SDS), FH SDS and improvement of FHSDS vs. H0SDS (ΔHSDS).Results: In the patients with IGF-I deficiency when compared with those with normal IGF-I secretion before treatment, significantly better FH SDS (−1.42±0.90 vs. −1.74±0.86, p=0.004) and ΔHSDS (1.64±1.01 vs. 1.32±1.05, p=0.010) were observed, despite similar H0SDS (− 3.07±0.78 vs. − 3.11±0.77, p=0.63) and GH peak (7.0±3.1 μg/l vs. 6.8±2.1 μg/l, p=0.55). The patients who achieved FH over 10th centile had significantly lower IGF-I SDS before treatment than those with FH below 10th centile (− 1.59±1.54 vs. − 1.20±1.64, p=0.04), despite similar GH peak (7.0±2.3 μg/l vs. 6.7±3.1 μg/l, p=0.45). The patients with ΔHSDS over the median value had significantly lower IGF-I SDS than those with ΔHSDS below the median value (− 1.59±1.71 vs. − 1.09±1.47, p<0.0001), despite similar GH peak (6.8±2.5 μg/l vs. 7.0±2.7 μg/l, p=0.86).Conclusion: In children with isolated, non-acquired GHD, secondary IGF-I deficiency is an important predictor of better GH therapy effectiveness.
Keywords: short stature; growth hormone stimulation tests; insulin-like growth factor-I; recombinant human growth hormone; final height